The general populations' understanding of first trimester miscarriage: a cross sectional survey. (November 2020) - McCarthy, C.M.; Meaney, S.; Rice, R.; Sheehan, J.; O'Donoghue, K.
Highlights: Less than 30% of those surveyed were aware of the incidence of miscarriage. The definition of recurrent miscarriage is also poorly understood. Family, friends and the internet are the main knowledge sources for miscarriage. Less than 1/6 of people engage with healthcare providers for miscarriage information. Abstract: Objectives: Miscarriage is a common, yet for many, devastating adverse pregnancy outcome. However, despite this the level of public knowledge on the topic is sub-optimal. We aimed to examine the general public's knowledge of miscarriage as well as their health information seeking behaviours associated with this topic. Study Design: We commissioned a national cross-sectional telephone survey of adults in the Republic of Ireland. 967 members of the general public consented to participate to this anonymised telephone survey. Sampling procedures ensured proportionality as per national standards. We examined respondents' definitions of miscarriage, its incidence and clinical findings, as well as the information seeking behaviours of the general population surrounding miscarriage. Results: 699 (72%) of respondents provided an estimate of miscarriage frequency, with 28% of respondents correctly estimating that miscarriage occurs in 21-30% of pregnancies, with 61% under-estimating the incidence. Men were three times more likely than women to under-estimate (aOR3.5; 95% CI 2.4-4.9), as were those without children (aOR 1.7; 95% CI 1.2-2.6), or those living in urban areas (aOR 1.6; 95%CI 1.0-2.4. One third of respondents (33%) believed that the risk of miscarriage was higher following only one miscarriage. While 83% of respondents knew someone who had experienced a miscarriage, just over one third had discussed the topic of miscarriage with a family member/friend. Conclusions: The general populations' knowledge of miscarriage, its incidence and associated factors is concerning, as are their health information seeking behaviours. Improving the level of knowledge of the general public could be achieved by adopting the topic into existing public health and education strategies. This will allow those experiencing miscarriage to frame their experience and expectations.